Effects of 1-hexyl-1-methylimidazolium iodide ionic liquid to poly(vinyl alcohol)–based solid polymer electrolyte - Christin Rina Ratri; Qolby Sabrina; Titik Lestariningsih; Salsabila Zakiyyah (SINERGI, 2022)
A solid polymer electrolyte (SPE) membrane has been fabricated using poly (vinyl alcohol) (PVA) as polymer host dissolved in deionized (DI) water. Lithium bis(oxalato) borate (LiBOB) electrolyte salt and 1-hexyl 1-methylimidazolium iodide (HMII) are incorporated into the membrane to contribute free ions, enhancing ionic conductivity. SPE was produced using the solution cast technique on Petri dishes. Then these slurries were dried at room temperature. The final product is a self-standing opaque membrane with visually homogenous surfaces. Further observation using FE-SEM revealed magnified images of membrane surfaces and cross-sections. Molecule interaction and crystallinity were observed using FT-IR and XRD. Impedance measured using EIS was used to calculate ionic conductivity. It was found that ionic conductivity of pure PVA film was 3.9×10-7 S/cm while ionic conductivity of SPE before and after ionic liquid addition was 4.77×10-7 S/cm and 2.66×10-6 S/cm.